2010
DOI: 10.1038/ajg.2010.154
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Chromogranin A Response to Octreotide Test: Prognostic Value for Clinical Outcome in Endocrine Digestive Tumors

Abstract: In GEP-NETs, plasma CgA is a reliable marker, and a >30% decrease after OT has a relevant prognostic meaning allowing the identification of the subgroup of patients most likely to be responsive to chronic SSAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 39 publications
3
30
1
3
Order By: Relevance
“…A variety of metrics have been assessed to evaluate the use of these markers. For example, a 30% decrease in CgA (from pretreatment levels) is considered predictive of SSA efficacy [38], while an increase in three consecutive measurements is considered to anticipate relapse after midgut surgery [39]. Some authors proposed that alterations of ≥25% in CgA may have good sensitivities (>75%) and specificities (>85%) for predicting disease events [33] while others suggested that levels twice the ULN (∼300 µg/l or 300 ng/ml) [32] or higher (≥600) [40] are effective predictors of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of metrics have been assessed to evaluate the use of these markers. For example, a 30% decrease in CgA (from pretreatment levels) is considered predictive of SSA efficacy [38], while an increase in three consecutive measurements is considered to anticipate relapse after midgut surgery [39]. Some authors proposed that alterations of ≥25% in CgA may have good sensitivities (>75%) and specificities (>85%) for predicting disease events [33] while others suggested that levels twice the ULN (∼300 µg/l or 300 ng/ml) [32] or higher (≥600) [40] are effective predictors of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results need confirmation in further prospective studies, validation in different settings such as digestive endocrine tumors (carcinoids) as well as testing with other treatment options such as peptide receptor radionuclide therapy and chemotherapy. Recent data from our own institution demonstrated that a ≥30% decrease in plasma CgA levels after acute octreotide administration has prognostic relevance for GEP-NEN patients as it allows discriminating between patients more likely to respond to chronic somatostatin analogue treatment and those likely to be unresponsive [17]. Accordingly, determining plasma CgA levels may be helpful in diagnosing NENs in a more precise way and can be relevant in delineating the prognosis by predicting disease recurrence, disease outcome and treatment effectiveness [18].…”
Section: Introductionmentioning
confidence: 99%
“…Высокий уровень ХГ-А чаще наблю-дается при НЭО средних отделов (midgut) ЖКТ, особенно при метастазах в печень, а также при нефункционирующих опухолях поджелудочной железы [44,45]. Следует от-метить, что повышение ХГ-А отмечается у пациентов, получающих терапию ингибито-рами протонной помпы, страдающих хрони-ческим атрофическим гастритом, почечной недостаточностью, застойной сердечной не-достаточностью и циррозом печени.…”
Section: лабораторные тестыunclassified